CROSSING BORDER TRANSACTIONS: UNRAVELING THE INFLUENCE OF E-COMMERCE ON THE ADVANCEMENT OF TRANSNATIONAL BUSINESS LAW - Napitupulu, Dona Regina (Transnational Business Law Journal, 2023)
Transnational transactions conducted through E-Commerce platforms open the gates of growth in the legal and economic spheres. In this regard, legislators should be able to create a transnational body of law as uniform rules and contractual patterns for commercial transactions conducted through e-commerce. Complex international business transaction activities such as investment, licensing, franchising, and so on have not escaped the development of e-commerce and the convenience that comes with it. The research uses a normative juridical approach and a descriptive analytical research method to describe the facts related to the problem being studied. Data collection is done through a literature study, searching for relevant data from various sources of primary and secondary legal materials related to the existing problems. The data is then analyzed qualitatively. Legal certainty in this case is rooted in matters that have been agreed upon by the parties and are mandated to continue to refer to the principles of international business transaction law and relevant international trade conventions or agreements. With the existence of e-contracts, agreements for transnational transactions can have permanent legal force and dispute resolution through litigation and non-litigation channels such as arbitration can be carried out virtually.